Profitability Meets Responsibility: The Role Of Board Gender Diversity In Shaping Corporate Tax Avoidance Behaviour - Nicklaus Stanley; Luky Patricia Widianingsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The diversity of the board of directors plays a critical role in the tax avoidance behaviour of a firm. However, up to date, there are no consistent findings regarding the effect of female directors on firms’ tax avoidance practices. Therefore, this research aims to obtain the latest empirical evidence as to whether board gender diversity plays a moderating role in the effect of profitability on corporate tax avoidance in the financial sector. This research uses secondary data obtained from financial companies’ annual and financial reports which are readily available on the IDX website and the company’s website from 2021 to 2023 using the panel data regression with moderation approach. The findings of this research analysis show predictor moderation, where board gender diversity acts as a predictor. Furthermore, board gender diversity and profitability are positively correlated to tax avoidance, whereas leverage and firm size do not affect the tax avoidance behaviours of financial companies.